2015
DOI: 10.1016/j.ajpath.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Global Deletion of Ankrd1 Results in a Wound-Healing Phenotype Associated with Dermal Fibroblast Dysfunction

Abstract: The expression of ankyrin repeat domain protein 1 (Ankrd1), a transcriptional cofactor and sarcomeric component, is strongly elevated by wounding and tissue injury. We developed a conditional Ankrd1(fl/fl) mouse, performed global deletion with Sox2-cre, and assessed the role of this protein in cutaneous wound healing. Although global deletion of Ankrd1 did not affect mouse viability or development, Ankrd1(-/-) mice had at least two significant wound-healing phenotypes: extensive necrosis of ischemic skin flaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Indeed, ANKRD1 is strongly elevated after wounding which suggests its role in the healing process [ 37 ]. Furthermore, it was recently shown that wound closure was significantly delayed in Ankrd1 knockout mice [ 38 ], lending further support to the role of ANKRD1 in tissue repair.…”
Section: Ankyrin Repeat Domain 1 Localization Interacting Partnermentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, ANKRD1 is strongly elevated after wounding which suggests its role in the healing process [ 37 ]. Furthermore, it was recently shown that wound closure was significantly delayed in Ankrd1 knockout mice [ 38 ], lending further support to the role of ANKRD1 in tissue repair.…”
Section: Ankyrin Repeat Domain 1 Localization Interacting Partnermentioning
confidence: 89%
“…Early work indicated the role of ANKRD1 in non-cardiac fibrotic responses where ANKRD1 transcripts and proteins are highly induced after dermal wounding in mice and its over-expression enhanced the healing process [ 37 ]. Moreover, Ankrd1 -knockout mice have been shown to be viable but display impaired wound healing that is characterized by dermal fibroblast dysfunction [ 38 ]. There is evidence that nuclear ANKRD1, in concert with nucleolin, functions in the wound repair process and modulates ECM remodeling via transcriptional regulation of matrix metalloproteinases gene expression [ 28 ].…”
Section: Pathological Cardiac Functions Of Ankrd1mentioning
confidence: 99%
“…ID3 acts as a transcriptional regulator inhibiting stem cell differentiation and promoting cell cycle progression [47]. In addition, a recent study showed that the loss of ANKRD1 function in mice resulted in delayed wound healing, suggesting its role in wounding and tissue injury [49]. Furthermore, Rho-related BTB domain-containing 3 (RHOBTB3) functions to promote the proteasomal degradation of hypoxia-inducible factors (HIFs), which are the main regulators of adaptive responses to low oxygen [50].…”
Section: Discussionmentioning
confidence: 99%
“…Ankrd1 , a transcriptional repressor of MMP13 [ 28 ], was highly upregulated in MRL/MpJ at 1-day post-injury, whereas only moderately changed in C57BL/6J and STR/ort ( Figure 4 B). Global deletion of Ankrd1 resulted in delayed excisional wound closure [ 29 ]. Deletion of Ankrd1 also resulted in moderate downregulation of Mmp2 and Mmp14 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%